Basalt fiber reinforced polyphenylene sulfide composite material and preparation method thereof

CN122917535APending Publication Date: 2026-10-16SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611097507.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

由于玄武岩纤维表面光滑、化学惰性较强,且表面活性位点较少,PPS树脂本身极性较弱,二者之间的界面相容性较差

Benefits of technology

本发明以特种工程塑料PPS为基体材料,充分发挥其耐高温、耐化学腐蚀、固有阻燃等优异性能,为复合材料在苛刻环境下的应用提供了基础保障;以玄武岩纤维为增强组分,充分利用其高模量、高强度以及优于玻璃纤维的耐温性能,可在保证复合材料耐热性的前提下,大幅提升其承载能力。在此基础上,建立玄武岩纤维/PPS二元复合体系,通过采用硅烷偶联剂KH-560的乙醇溶液对玄武岩纤维进行表面处理,使偶联剂分子一端的硅羟基(Si-OH)与纤维表面的硅羟基发生缩合反应形成Si-O-Si共价键,另一端的有机官能团(环氧基)与PPS分子链形成化学键合或强相互作用,实现纤维与基体间的化学键连接;同时经偶联剂处理后纤维表面粗糙度显著提高,PPS熔体浸润并填充于纤维表面的微观凹坑中,冷却固化后形成机械铆合结构,二者协同作用使两组分形成牢固的界面结合层。通过上述界面优化设计,充分发挥PPS基体的韧性与玄武岩纤维的刚性优势,实现复合材料高强度、高模量的性能目标。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122917535A_ABST
    Figure CN122917535A_ABST
Patent Text Reader

Abstract

The application discloses a basalt fiber reinforced polyphenylene sulfide composite material and a preparation method thereof, and comprises the following steps: step 1), a silane coupling agent is weighed, mixed and dissolved with anhydrous ethanol, deionized water is added, and stirring is conducted to prepare a uniform coupling agent solution; the coupling agent solution is uniformly mixed with basalt fibers, and is placed to allow the coupling agent to fully infiltrate the surface of the fibers; then, drying treatment is conducted to completely volatilize the ethanol, and surface-modified basalt fibers are obtained; step 2), polyphenylene sulfide raw materials are placed in a drying device to conduct drying treatment to remove water; step 3), the dried polyphenylene sulfide raw materials and the surface-modified basalt fibers are put into a mixing device to conduct mechanical mixing, and a premix is obtained; the premix is added into a double-screw extruder to conduct melt blending and extrusion granulation, and the basalt fiber reinforced polyphenylene sulfide composite material is obtained. The basalt fiber reinforced polyphenylene sulfide composite material fully plays the reinforcing role of the basalt fibers and improves the comprehensive performance of the composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer composite modification technology, specifically relating to a basalt fiber reinforced polyphenylene sulfide composite material and its preparation method. Background Technology

[0002] Polyphenylene sulfide (PPS) is a type of polyarylene sulfide. Its molecular backbone consists of alternating benzene rings and sulfur atoms. The benzene ring structure gives PPS rigidity, while the sulfide bonds provide flexibility. PPS possesses excellent high-temperature resistance, chemical corrosion resistance, inherent flame retardancy, and good electrical insulation properties. It also exhibits high rigidity and low molding shrinkage, leading to its widespread application in aerospace, automotive manufacturing, electronics, and chemical corrosion protection. However, pure PPS resin also has some significant performance drawbacks. For example, its high crystallinity results in poor toughness and relatively low impact strength, and its material cost is relatively high. These limitations, to some extent, restrict the widespread application of PPS in certain high-end structural components.

[0003] To address the aforementioned shortcomings, industrial applications typically employ fiber reinforcement modification to improve the mechanical properties and thermal stability of PPS. Commonly used reinforcements include glass fiber (GF) and carbon fiber (CF). GF-reinforced PPS composites can improve strength and modulus to a certain extent, with relatively controllable costs. However, the interfacial bonding between the glass fiber and the PPS matrix is ​​somewhat insufficient, easily leading to interfacial debonding under stress. While carbon fiber-reinforced PPS can achieve superior specific strength and modulus, the high production cost of carbon fiber and the energy-intensive preparation process keep the composite material price high, making it difficult to meet the cost-effectiveness requirements of general industrial applications.

[0004] Basalt fiber (BF) is a new type of green, high-performance inorganic fiber made from the melting and drawing of natural basalt rock. It features environmentally friendly characteristics such as a pollution-free production process and biodegradable waste. In terms of performance, basalt fiber boasts advantages such as good mechanical properties, high temperature resistance, good abrasion resistance, and chemical stability. Its overall performance falls between that of glass fiber and carbon fiber, but its cost is far lower than that of carbon fiber.

[0005] In existing technologies, such as Castro-Cabrera M, García-Rodríguez S, Jiménez-Suárez A, et al. Correlations between micro mechanical analyses and macro-scale mechanical properties of PPS / basalt fiber composites designed from commingled yarns[J]. Polymer Testing, 2025, 108894. DOI: 10.1016 / j.polymertesting.2025.108894, the composite of basalt fiber and PPS still faces key technical bottlenecks. Because basalt fiber has a smooth surface, strong chemical inertness, and few surface active sites, while PPS resin itself has weak polarity, the interfacial compatibility between the two is poor. Without special interfacial modification treatment, it is difficult for basalt fiber and PPS matrix to form a strong chemical bond, resulting in the fiber existing independently in the matrix, significantly reducing the reinforcing effect. To address this issue, extensive research has been conducted on interface optimization. The results show that by surface treating basalt fibers or using functionalized sizing agents, the interfacial shear strength (IFSS) between the fibers and PPS can be significantly improved, with a maximum improvement of up to 360%, thereby enhancing the macroscopic mechanical properties of the composite material by more than 60%.

[0006] In summary, basalt fiber, as a reinforcing material that combines cost-effectiveness and environmental friendliness, has broad application prospects in the field of PPS modification. However, achieving a good interfacial bond between basalt fiber and PPS while steadily improving the overall mechanical properties of the composite material remains a technical problem to be solved in current research. Summary of the Invention

[0007] To overcome the problems existing in the prior art, the present invention aims to provide a basalt fiber reinforced polyphenylene sulfide composite material and its preparation method. By optimizing the fiber surface treatment process and melt blending conditions, the interfacial compatibility between basalt fiber and polyphenylene sulfide resin matrix is ​​improved, thereby giving full play to the reinforcing effect of basalt fiber and improving the comprehensive performance of the composite material, especially meeting the requirements for use under friction and wear conditions.

[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A basalt fiber reinforced polyphenylene sulfide composite material uses a special engineering polymer material with high temperature resistance and excellent comprehensive performance as the continuous phase and a high-modulus inorganic fiber material as the reinforcing component; the reinforcing component is uniformly distributed in the form of a dispersed phase inside the continuous phase; the composite material structure is a composite system in which the reinforcing fibers are uniformly distributed in a lattice.

[0009] The reinforcing component is fibrous in shape, with an aspect ratio between 10 and 500; the mass percentage of the reinforcing fiber in the special engineering polymer material (continuous phase) is between 5% and 40%.

[0010] The special engineering polymer material (continuous phase) is polyphenylene sulfide (PPS); the reinforcing component material is basalt fiber (BF).

[0011] A method for preparing a basalt fiber reinforced polyphenylene sulfide composite material includes the following steps: Step 1) Surface treatment of basalt fiber: Weigh 1.5% of the silane coupling agent according to the mass of basalt fiber in the formula, mix it with anhydrous ethanol at a mass ratio of 1:8 to dissolve it, then add 0.5 to 1 times the mass of the coupling agent in deionized water, and stir to prepare a uniform coupling agent solution; mix the coupling agent solution with the basalt fiber evenly, let it stand for 24 hours to allow the coupling agent to fully wet the fiber surface; then perform a drying treatment to allow the ethanol to completely evaporate, and obtain surface-modified basalt fiber; Step 2) Raw material drying: Place the polyphenylene sulfide (PPS) raw material in a drying device for drying to remove moisture; Step 3) Melt blending and granulation: The dried polyphenylene sulfide raw material and the surface-modified basalt fiber obtained in step 1) are put into a mixing equipment for mechanical mixing to obtain a premix; the premix is ​​added to a twin-screw extruder for melt blending and extrusion granulation, and the extrusion granulation temperature is controlled at 280~310℃ to obtain basalt fiber reinforced PPS composite material blend granules.

[0012] In step 1), the silane coupling agent is at least one of γ-aminopropyltriethoxysilane (KH-550), γ-glycidoxypropyltrimethoxysilane (KH-560), or γ-methacryloyloxypropyltrimethoxysilane (KH-570).

[0013] The drying conditions in step 2) are vacuum drying at 80~100℃ for 2~4 hours.

[0014] In step 3), the screw speed of the twin-screw extruder is 150~300 rpm, and the feeding speed is 5~15 kg / h.

[0015] The beneficial effects of this invention are: This invention uses PPS, a special engineering plastic, as the matrix material, fully leveraging its excellent properties such as high temperature resistance, chemical corrosion resistance, and inherent flame retardancy, providing a fundamental guarantee for the application of composite materials in harsh environments. Basalt fiber is used as the reinforcing component, fully utilizing its high modulus, high strength, and superior temperature resistance compared to glass fiber, significantly improving the load-bearing capacity of the composite material while ensuring its heat resistance. Based on this, a basalt fiber / PPS binary composite system is established. The basalt fiber is surface-treated with an ethanol solution of the silane coupling agent KH-560, causing the silanol groups (Si-OH) at one end of the coupling agent molecule to condense with the silanol groups on the fiber surface to form Si-O-Si covalent bonds. The organic functional groups (epoxy groups) at the other end form chemical bonds or strong interactions with the PPS molecular chains, achieving chemical bonding between the fiber and the matrix. Simultaneously, the surface roughness of the fiber is significantly improved after coupling agent treatment, allowing the PPS melt to wet and fill the microscopic pits on the fiber surface. After cooling and solidification, a mechanically bonded structure is formed. The synergistic effect of these two components creates a strong interfacial bonding layer. Through the above interface optimization design, the toughness of the PPS matrix and the rigidity of the basalt fiber are fully utilized to achieve the performance goals of high strength and high modulus of the composite material.

[0016] Using a specific ratio of silane coupling agent ethanol solution, KH-560 molecules, containing a hydrolyzable alkoxy group (-OR) at one end, hydrolyze in an ethanol-water system to generate active silanol groups (Si-OH). Basalt fibers are impregnated for up to 24 hours, allowing the coupling agent molecules to overcome the physical adsorption energy barrier, continuously migrate and spread to the fiber surface, and tightly adsorb onto the active sites on the fiber surface. During the subsequent drying process, the silanol groups (Si-OH) adsorbed on the fiber surface undergo a dehydration condensation reaction with the silanol groups (Si-OH) on the basalt fiber surface, forming strong Si-O-Si covalent bonds. This anchors the coupling agent molecules to the fiber surface via chemical bonds, forming a uniform and dense organic molecular layer. This organic molecular layer, on the one hand, firmly bonds to the surface of basalt fibers through Si-O-Si covalent bonds, altering the surface physicochemical properties of the fibers; on the other hand, its active functional groups (the epoxy groups of KH-560) can chemically react with the end groups of PPS molecular chains or form strong polar interactions / physical entanglements during melt blending, thereby establishing an effective molecular bridge between the fibers and the PPS matrix. This effectively solves the technical challenges of large polarity differences and poor interfacial compatibility between basalt fibers and the PPS matrix, preventing fiber debonding and pull-out under stress, and ensuring that the reinforcing effect is fully realized.

[0017] The excellent interfacial bonding allows the reinforcing effect of basalt fibers to be fully utilized, resulting in significantly improved tensile strength, flexural strength, and flexural modulus of the composite material compared to pure PPS. Furthermore, the composite material prepared by this invention, after being injection molded into friction test specimens, exhibits a low coefficient of friction and excellent wear resistance, indicating that the material possesses both good mechanical load-bearing capacity and tribological properties, making it particularly suitable for manufacturing mechanical components such as bearings, gears, and sliders that require long-term service under frictional conditions.

[0018] The basalt fiber reinforced PPS composite material of this invention has high strength, high modulus, good heat resistance and tribological properties, and the cost is relatively controllable. It has broad development prospects in application fields with high requirements for comprehensive material performance and cost-effectiveness, such as the automotive industry, electronics, machinery manufacturing and aerospace. Attached Figure Description

[0019] Figure 1 This is a scanning electron microscope (SEM) image of the surface morphology of the unmodified basalt fibers of this invention.

[0020] Figure 2 This is a scanning electron microscope (SEM) image of the surface morphology of KH560 basalt fibers according to the present invention.

[0021] Figure 3 This is a scanning electron microscope (SEM) image of the fracture surface morphology of the basalt fiber reinforced PPS composite material of the present invention. Detailed Implementation

[0022] The present invention will now be described in further detail with reference to the accompanying drawings.

[0023] Example 1 1) Surface treatment of basalt fiber: Weigh 40g of basalt fiber (BF), weigh 1.5% (0.6g) of silane coupling agent KH-560 according to the fiber weight, dissolve it in 20ml of anhydrous ethanol, and stir to prepare a uniform coupling agent solution; mix the coupling agent solution with the basalt fiber evenly, let it stand for 24 hours to allow the coupling agent to fully wet the fiber surface; then dry it at 80℃ for 2 hours to allow the ethanol to completely evaporate, and obtain surface-modified basalt fiber; 2) Raw material drying: Weigh 60g of polyphenylene sulfide (PPS) resin, place it in a vacuum drying oven, and vacuum dry it at 100℃ for 3 hours to remove moisture; 3) Melt blending and granulation: The dried PPS raw material and the surface-modified basalt fiber obtained in step 1) are put into a high-speed mixer and mechanically mixed for 5 minutes to obtain a premix; the premix is ​​added to a twin-screw extruder for melt blending and extrusion granulation, and the extrusion granulation temperature is controlled at 270-310℃, the screw speed is 200rpm, and the feeding speed is 10kg / h to obtain the blended granules of basalt fiber reinforced PPS composite material; Example 2 1) Surface treatment of basalt fiber: Weigh 20g of basalt fiber (BF), weigh 1.5% (0.3g) of silane coupling agent KH-560 according to the fiber weight, dissolve it in 20ml of anhydrous ethanol, and stir to prepare a uniform coupling agent solution; mix the coupling agent solution with the basalt fiber evenly, let it stand for 24 hours to allow the coupling agent to fully wet the fiber surface; then dry it at 80℃ for 2 hours to allow the ethanol to completely evaporate, and obtain surface-modified basalt fiber; 2) Raw material drying: Weigh 80g of polyphenylene sulfide (PPS) resin, place it in a vacuum drying oven, and vacuum dry it at 100℃ for 3 hours to remove moisture; 3) Melt blending and granulation: The dried PPS raw material and the surface-modified basalt fiber obtained in step 1) are put into a high-speed mixer and mechanically mixed for 5 minutes to obtain a premix; the premix is ​​added to a twin-screw extruder for melt blending and extrusion granulation, and the extrusion granulation temperature is controlled at 270-310℃, the screw speed is 200rpm, and the feeding speed is 10kg / h to obtain the blended granules of basalt fiber reinforced PPS composite material; Comparative Example 1 This comparative example provides a method for preparing pure polyphenylene sulfide (PPS) material as a blank control. 100g of PPS resin was weighed, vacuum dried at 100℃ for 3 hours, and directly added to a twin-screw extruder for melt extrusion granulation, following the same procedure as step 3) in Example 1, to obtain pure PPS granules; injection molding was then performed on standard test specimens.

[0024] Comparative Example 2 This comparative example provides a method for preparing basalt fiber reinforced PPS composite material without surface treatment, to compare the effect of interface treatment.

[0025] 1) Weigh 20g of basalt fiber that has only been dried and has not undergone any surface treatment, and mix it with 80g of dried PPS resin; 2) Add the mixture to a twin-screw extruder for melt blending and granulation, with the process conditions the same as in Example 1. 3) Following the above method, test the friction coefficient and mechanical strength of the four types of high-performance lightweight design materials in Example 1, Example 2, Comparative Example 1, and Comparative Example 2, as shown in Table 1 below.

[0026] Table 1. Friction coefficients of different materials under a load of 200N Composite materials Example 1 Example 2 Comparative Example 1 Comparative Example 2 Coefficient of friction (μ) 0.23 0.26 0.38 0.24 By comparing and analyzing the material friction coefficients in Table 1, it can be seen that, due to the good self-lubricating properties of BF, adding BF can effectively reduce the friction coefficient of PPS, and the friction coefficient shows a decreasing trend with the increase of BF content.

[0027] To further verify the load-bearing capacity of BF-reinforced PPS composites, the flexural strength, tensile strength, and impact strength of each composite material were tested using a universal testing machine. The test results for these three properties of each composite material are shown in Table 2 below.

[0028] Table 2 Mechanical properties of different composite materials Composite materials Example 1 Example 2 Comparative Example 1 Comparative Example 2 Bending strength (MPa) 238 185.6 94.8 127 Tensile strength (MPa) 170 118 81.3 80.5 Impact strength (KJ / m2) 27 14 8.6 13 Comparative analysis of the mechanical properties in Table 2 shows that, compared with Comparative Example 1 (pure PPS material), the addition of basalt fiber significantly improves the flexural strength, tensile strength, and impact strength of the PPS composite material. With increasing basalt fiber content, the mechanical properties of the composite material further improve; for example, the flexural strength, tensile strength, and impact strength of Example 1 (40% fiber content) are significantly higher than those of Example 2 (20% fiber content). However, at the same fiber content (20%), Example 2, treated with a silane coupling agent, shows a slight increase in flexural strength, tensile strength, and impact strength compared to the untreated Comparative Example 2. This indicates that the coupling agent treatment effectively improves the interfacial bonding between the fiber and the PPS matrix, resulting in a more significant reinforcing effect.

[0029] As can be seen from the above, the basalt fiber reinforced PPS composite material provided by the present invention achieves efficient synergy between the fiber and the matrix through interface modification, which greatly improves the load-bearing capacity while maintaining the excellent heat resistance of PPS, and the cost is lower than that of the carbon fiber reinforced system, and has broad application prospects.

[0030] like Figure 1 As shown in the scanning electron microscope (SEM) image of the surface morphology of the unmodified basalt fiber of the present invention, the surface of the unmodified basalt fiber is smooth and flat, with no obvious attachments and few active functional groups, which is not conducive to forming an effective interface bond with the polyphenylene sulfide (PPS) resin matrix.

[0031] like Figure 2As shown in the scanning electron microscope (SEM) image, the surface morphology of basalt fibers modified with KH-560 silane coupling agent is as follows: after KH-560 treatment, the fiber surface is uniformly coated with a coupling agent film and has a large number of granular protrusions, resulting in a significant increase in surface roughness. This roughened structure is beneficial for the mechanical bonding and interfacial interlocking between the fiber and the PPS matrix. At the same time, the organic functional groups on the coupling agent molecular chain can physically entangle or chemically bond with the PPS molecular chain, thereby effectively improving the interfacial bonding strength.

[0032] like Figure 3 As shown in the scanning electron microscope (SEM) image of the fracture surface morphology of the basalt fiber reinforced PPS composite material of the present invention, the fracture surface of the composite material exhibits typical ductile fracture characteristics. The fibers are uniformly dispersed in the PPS matrix, with most fiber surfaces tightly coated with PPS resin. The fiber pull-out length is relatively short, and the inner walls of the pores left after pull-out are adhered with a large amount of resin residue, with no obvious smooth debonding interface observed. This indicates that a strong interfacial bonding layer is formed between the fibers and the PPS matrix. Under stress, cracks are difficult to propagate along the interface, but instead penetrate the interface into the matrix phase, thereby effectively transferring and dispersing stress, which macroscopically manifests as a significant improvement in the mechanical properties of the composite material.

Claims

1. A basalt fiber reinforced polyphenylene sulfide composite material, characterized in that, The composite material uses a special engineering polymer material as the continuous phase and an inorganic fiber material as the reinforcing component; the reinforcing component is uniformly distributed in the interior of the continuous phase in the form of a dispersed phase; the composite structure is a composite system in which the reinforcing fibers are uniformly distributed in a lattice.

2. The basalt fiber reinforced polyphenylene sulfide composite material according to claim 1, characterized in that, The reinforcing component is fibrous in shape, with an aspect ratio between 10 and 500; the mass percentage of the reinforcing fiber in the special engineering polymer material is between 5% and 40%.

3. The basalt fiber reinforced polyphenylene sulfide composite material according to claim 1, characterized in that, The special engineering polymer material is polyphenylene sulfide; the reinforcing component material is basalt fiber.

4. A method for preparing a basalt fiber reinforced polyphenylene sulfide composite material according to any one of claims 1-3, characterized in that, Includes the following steps: Step 1): Weigh 1.5% of the silane coupling agent according to the mass of basalt fiber in the formula, mix it with anhydrous ethanol at a mass ratio of 1:8 to dissolve it, then add 0.5 to 1 times the mass of the coupling agent in deionized water, and stir to prepare a uniform coupling agent solution; mix the coupling agent solution with the basalt fiber evenly, let it stand to allow the coupling agent to fully wet the fiber surface; then perform a drying treatment to allow the ethanol to completely evaporate, and obtain surface-modified basalt fiber; Step 2): Place the polyphenylene sulfide raw material in a drying device for drying to remove moisture; Step 3): The dried polyphenylene sulfide raw material and the surface-modified basalt fiber obtained in Step 1) are put into a mixing equipment for mechanical mixing to obtain a premix; the premix is ​​added to a twin-screw extruder for melt blending and extrusion granulation, and the extrusion granulation temperature is controlled at 280~310℃ to obtain basalt fiber reinforced polyphenylene sulfide composite material.

5. The method for preparing a basalt fiber reinforced polyphenylene sulfide composite material according to claim 4, characterized in that, In step 1), the silane coupling agent is at least one of γ-aminopropyltriethoxysilane (KH-550), γ-glycidoxypropyltrimethoxysilane (KH-560), or γ-methacryloyloxypropyltrimethoxysilane (KH-570).

6. The method for preparing a basalt fiber reinforced polyphenylene sulfide composite material according to claim 4, characterized in that, The drying conditions in step 2) are vacuum drying at 80~100℃ for 2~4 hours.

7. The method for preparing a basalt fiber reinforced polyphenylene sulfide composite material according to claim 4, characterized in that, In step 3), the screw speed of the twin-screw extruder is 150~300 rpm, and the feeding speed is 5~15 kg / h.